Five Decade of Religious Family Counseling: Past, Present, and Future Direction - Hartanto, Dody; Suci, Rohmadheny Prima; Purwanta, Edy; Fauziah, Mufied (Buletin Konseling Inovatif, 2025)
Integrating religion and spirituality into therapy raises ethical concerns like respecting client beliefs, setting boundaries, and addressing value conflicts. Research on religious family therapy can inform ethical guidelines and best practices. However, despite extensive research on religious family therapy in Indonesia, these studies are not visible in the Scopus database. The aim of this study was to identify research trends, hot topics, and new areas in the field of religious family therapy. This study used bibliometric analysis in the Scopus database. The keywords used are “religious family therapy” or “spiritual family therapy”. Articles to be analyzed were previously identified and filtered using the PRISMA analysis model. A total of 398 articles were selected independently and then analyzed using bibliometrics with the help of Scopus and VOSviewer. The highest number of publications on religious family therapy was recorded in 2022. The country that contributes the most to the topic of religious family therapy is the United States. North Dakota State University is the affiliate with the most publications. The journal with the largest number of article publications is the Journal of Religion and Health. McGeorge, C.R. as the author who contributed the most to publications on the topic of religious family therapy and the keywords that often appear in research titles on the theme of religious family therapy are human, human article and family. This finding has provided the opportunities for religious countries like Indonesia to encourage further research on the topic of religious family therapy in the Scopus database.